2024
DOI: 10.1152/physrev.00011.2023
|View full text |Cite
|
Sign up to set email alerts
|

CD36 as a gatekeeper of myocardial lipid metabolism and therapeutic target for metabolic disease

Jan F. C. Glatz,
Lisa C. Heather,
Joost J. F. P. Luiken

Abstract: The multifunctional membrane glycoprotein CD36 is expressed in different types of cells and plays a key regulatory role in cellular lipid metabolism. CD36 facilitates the cellular uptake of long-chain fatty acids, mediates lipid signaling, and regulates storage and oxidation of lipids in various tissues with active lipid metabolism. CD36 deficiency leads to marked impairments in peripheral lipid metabolism, which consequently impacts on the cellular utilization of multiple different fuels, due to the integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 300 publications
(390 reference statements)
1
1
0
Order By: Relevance
“…Altogether these data support the notion that these therapeutic bounties are driven by the agonistic stimulation of myocardial and extra-myocardial CD36 and/or GHSR1a receptors by activating survival pathways, downregulating fibrogenic cytokines, and optimizing energetic homeostasis shunts that cooperate in cellular survival (Hosoda, 2022;Shu et al, 2022;Glatz et al, 2023). Whether these cytoprotective and anti-fibrotic effects are solely consequent to the stimulation of GHS-R1a has been debated (Yuan et al, 2021) and is beyond the scope of our study.…”
Section: Discussionsupporting
confidence: 81%
“…Altogether these data support the notion that these therapeutic bounties are driven by the agonistic stimulation of myocardial and extra-myocardial CD36 and/or GHSR1a receptors by activating survival pathways, downregulating fibrogenic cytokines, and optimizing energetic homeostasis shunts that cooperate in cellular survival (Hosoda, 2022;Shu et al, 2022;Glatz et al, 2023). Whether these cytoprotective and anti-fibrotic effects are solely consequent to the stimulation of GHS-R1a has been debated (Yuan et al, 2021) and is beyond the scope of our study.…”
Section: Discussionsupporting
confidence: 81%
“…In their previous research, the authors had shown that palmitate entry in the cells through endocytosis of membrane-derived vesicles containing CD36 led to the inhibition of the endosomal proton pumping activity of v-ATPase (vacuolar-type H + -ATPase) and resulted in the alkalinization of endosomes. 5 The consequence is that deacidified endosomes can no longer serve as CD36 storage compartment and CD36 is translocated back to the membrane where it interacts with the TLR4 (Toll-like receptor 4) triggering an inflammatory response to lipid overload; see also Glatz et al 6 for a recent review on these mechanisms and a broader view on the regulatory role of CD36 in cellular lipid metabolism. In the present study, the authors also identify the C18:1-enriched diacylglycerols as the main harmful lipid mediators of lipid-induced cardiomyopathy.…”
Section: Article See P 505mentioning
confidence: 99%